Objective correlates and determinants of bicycle commuting propensity in an urban environment. (October 2015) - Cole-Hunter, T.; Donaire-Gonzalez, D.; Curto, A.; Ambros, A.; Valentin, A.; Garcia-Aymerich, J.; Martínez, D.; Braun, L.M.; Mendez, M.; Jerrett, M.; Rodriguez, D.; de Nazelle, A.; et al.
Highlights: We performed a travel survey in the Mediterranean city of Barcelona, Spain. Our study recruitment design surveyed a relatively-high proportion of bicyclists. We ascertained urban environmental determinants for bicycle commuting using GIS. Bicycle sharing stations and greenness were motivators for bicycle commuting. Public transport stations and elevation were deterrents for bicycle commuting. Abstract: Objective: Bicycle use for commuting is being encouraged not only to address physical inactivity, but also vehicular congestion, air pollution and climate change. The current study aimed to ascertain the urban environmental correlates and determinants of bicycle use for commuting (bicycle commuting) among the working or studying population in Barcelona, Spain. Methods: Adults ( n = 769; 52% females) recruited whilst commuting within Barcelona (Spain) responded to a comprehensive telephone survey concerning their travel behaviour. Based upon responses collected from June 2011 to May 2012, participants were categorised into four groups: frequent bicyclists, infrequent bicyclists, willing non-bicyclists, and unwilling non-bicyclists. The determinants of frequency and willingness (propensity) to commute by bicycle were assessed by multinomial logistic regression models adjusted for potential confounders and covariates. Results: The number of public bicycle stations surrounding the home address and amount of greenness surrounding the work/study address were significant positive determinants of bicycle commuting propensity. On the other hand, the number of public transport stations surrounding the home address and elevation of the work/study address were significant negative determinants of bicycle commuting propensity. Individual age, education level, gender, nationality, physical activity level and commute distance significantly affected this propensity. Conclusion: Greater availability of public bicycle stations and higher levels of urban greenness may increase bicycle use by adults commuting within a city such as Barcelona, Spain. Electrically-assisted public bicycles may address the challenge of elevation, making this system a more competitive mode against traditional motorised public transport.